Associations between Narrow Angle and Adult Anthropometry: The Liwan Eye Study. (June 2014) - Jiang, Yuzhen; He, Mingguang; Friedman, David S.; Khawaja, Anthony P.; Lee, Pak Sang; Nolan, Winifred P.; Yin, Qiuxia; Foster, Paul J.
Abstract Purpose: To assess the associations between narrow angle and adult anthropometry. Methods: Chinese adults aged 50 years and older were recruited from a population-based survey in the Liwan District of Guangzhou, China. Narrow angle was defined as the posterior trabecular meshwork not visible under static gonioscopy in at least three quadrants (i.e. a circumference of at least 270°). Logistic regression models were used to examine the associations between narrow angle and anthropomorphic measures (height, weight and body mass index, BMI). Results: Among the 912 participants, lower weight, shorter height, and lower BMI were significantly associated with narrower angle width (tests for trend: mean angle width in degrees vs weight p < 0.001; vs height p < 0.001; vs BMI p = 0.012). In univariate analyses, shorter height, lower weight and lower BMI were all significantly associated with greater odds of narrow angle. The crude association between height and narrow angle was largely attributable to a stronger association with age and sex. Lower BMI and weight remained significantly associated with narrow angle after adjustment for height, age, sex, axial ocular biometric measures and education. In analyses stratified by sex, the association between BMI and narrow angle was only observed in women. Conclusion: Lower BMI and weight were associated with significantly greater odds of narrow angle after adjusting for age, education, axial ocular biometric measures and height. The odds of narrow angle increased 7% per 1 unit decrease in BMI. This association was most evident in women.